Classroom, a teenage view - Moreno, Joaquim, 1973-; Poças Martins, Ivo, 1980- (Barcelona : Puente Editores, 2024)
The aim for this book is for it to become a reference in the ongoing debate about spaces of learning and education: it presents contributions from experts in the relevant fields, along with the research underlying the project, select case studies and testimony of the iterations of this initiative in France, Portugal and Belgium. It cements the optimistic view shared by the project's participants over the years: the believe that public education is a foundation of contemporary Europe, and that the right architectural and design solutions really can enhance and multiply its power.
Keywords: Education